Follicular wave emergence in Santa Ines ewes subjected to long-term, progesterone-based estrous synchronization protocols at different times of the year - Oliveira, M. E. F. [UNESP]; Ayres, H.; Oliveira, L. G. [UNESP]; Oba, E. [UNESP]; Kridli, R. T.; Bartlewski, P. M.; Fonseca, J. F.; Bicudo, S. D. [UNESP]; Vicente, W. R. R. (Elsevier B.V., 2016)
This study was conducted to document the pattern of antral follicular wave emergence throughout the 14-day, progesterone (P-4)-based estrous synchronization protocol in ewes that were maintained in subtropical conditions, during the period of increasing day lengths (ID), decreasing day lengths (DD), and the transitional period (TP). In addition, the influence of ovarian status (i.e., size of ovarian antral follicles and the presence of corpora lutea) at the outset of P-4 treatment on ensuing ovarian follicular wave development was examined. Sexually mature Santa Ines ewes (n =70) were subjected to one of the two estrous synchronization protocols in the three seasons. On Day 0, the ewes received an i.m. injection of prostaglandin F-2 alpha and an intravaginal P4-releasing device that remained in place for 14days (G-1CIDR) or was replaced on Day 7 (G-2CIDR). Daily ultrasonography of ovaries was conducted from Days 0 to 15. Mean (+/- SEM) numbers of follicular waves per ewe were 3.7 +/- 0.1 and 3.6 +/- 0.1 for G-1CIDR and G-2CIDR (P > 0.05). The number of emerging follicular waves was greater (P<0.05) during the ID period than during the TP and DD periods (4.0 +/- 0.1, 3.4 +/- 0.1 and 3.6 +/- 0.1, respectively). The presence of medium-sized antral follicles (4.0 to 5.75 mm) in the absence of corpora lutea at the time of CIDR insertion tended to advance follicular wave emergence. Although the long-term P-4 treatment was not originally designed to synchronize follicular waves, there was a distinctive pattern of follicular wave dynamics during the period of application of CIDRs that was affected mainly by the number of emerging follicular waves and ovarian status at CIDR insertion. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Ewe; Follicular dynamics; Estrus synchronization; Progesterone; Superovulation